2019
DOI: 10.1096/fj.201900444r
|View full text |Cite
|
Sign up to set email alerts
|

Low availability of choline in utero disrupts development and function of the retina

Abstract: Adequate supply of choline, an essential nutrient, is necessary to support proper brain development. Whether prenatal choline availability plays a role in development of the visual system is currently unknown. In this study, we addressed the role of in utero choline supply for the development and later function of the retina in a mouse model. We lowered choline availability in the maternal diet during pregnancy and assessed proliferative and differentiation properties of retinal progenitor cells (RPCs) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 86 publications
1
12
0
Order By: Relevance
“…The retina is derived from the neuroepithelium of the ventral diencephalon [ 65 ]. Choline also facilitates optimal retinal development [ 66 , 67 ]. Choline acetyltransferase-expressing retinal amacrine cells exist in the retinas of human and vertebral animals [ 68 ].…”
Section: Choline In the Retinamentioning
confidence: 99%
See 1 more Smart Citation
“…The retina is derived from the neuroepithelium of the ventral diencephalon [ 65 ]. Choline also facilitates optimal retinal development [ 66 , 67 ]. Choline acetyltransferase-expressing retinal amacrine cells exist in the retinas of human and vertebral animals [ 68 ].…”
Section: Choline In the Retinamentioning
confidence: 99%
“…The choline acetyltransferase in the outer plexiform layer of the retina slowly reduces during larval development [ 69 ]. Choline plays a critical role in the regulation of the temporal progression of retinogenesis, and adequate choline supplementation is essential for optimal development of the visual system [ 67 ]. Choline deficiency leads to impairments in the differentiation of retinal neuronal cells, such as the densities of early born retinal ganglion cells, amacrine and horizontal cells, and cone photoreceptor precursors [ 67 ].…”
Section: Choline In the Retinamentioning
confidence: 99%
“…For example, piglets born to choline-deficient mothers had lower brain weight, volume, and less white and grey matter at 30 days of age as compared to control piglets [73,74,75]. A recent study reported that low choline during gestation also disrupted retinal development and visual function in mice [77]. Possible mechanisms by which maternal choline influences offspring neurodevelopment and cognitive function are related to (i) the use of choline for phospholipid membrane synthesis; (ii) facilitation of DHA uptake [21]; (iii) myelination of neurons during early development [13,78]; (iv) alterations in hippocampal acetylcholine metabolism [28,79]; (v) modulation of neurogenesis and neuronal differentiation [76,77]; and (vi) modifications on epigenetic marks that govern hippocampal angiogenesis and cellular proliferation [33,34].…”
Section: Choline and Pregnancy Outcomesmentioning
confidence: 99%
“…A recent study reported that low choline during gestation also disrupted retinal development and visual function in mice [77]. Possible mechanisms by which maternal choline influences offspring neurodevelopment and cognitive function are related to (i) the use of choline for phospholipid membrane synthesis; (ii) facilitation of DHA uptake [21]; (iii) myelination of neurons during early development [13,78]; (iv) alterations in hippocampal acetylcholine metabolism [28,79]; (v) modulation of neurogenesis and neuronal differentiation [76,77]; and (vi) modifications on epigenetic marks that govern hippocampal angiogenesis and cellular proliferation [33,34]. All of these choline-induced outcomes ultimately influence cellular proliferation, differentiation, morphology, dendritic branching, neurogenesis, and potentiation of the offspring hippocampus [76,80,81,82].…”
Section: Choline and Pregnancy Outcomesmentioning
confidence: 99%
“…Evidence suggests that, for a significant number of individuals, choline consumption is far below the adequate intake (9) . For example, only 7 % of women in developed countries and fewer in developing countries consistently achieve the daily recommended intake of choline (11) . Growing evidence highlights a critical role for choline in health and links inadequate choline intake to impaired liver and muscle function in humans and other animals (12) .…”
mentioning
confidence: 99%